PERAN BANK DIGITAL DALAM KEHIDUPAN MAHASISWA - Achmarul Fajar; Akhmad Maulana Arizal; Nurul Hidayah Ansori; Ach Lutfiadi (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to analyze the role of digital banks in the lives of university students, particularly in supporting financial management, facilitating transactions, and improving financial inclusion among young adults. The research employed a quantitative descriptive approach using survey methods to collect primary data from undergraduate students who actively use digital banking services. Data were obtained through structured questionnaires distributed online, while secondary data were gathered from academic journals, official reports, and relevant literature concerning digital banking and student financial behavior. The data collection process involved identifying respondents, distributing questionnaires, validating responses, and conducting statistical analysis to identify patterns of digital bank usage and its impact on students’ daily financial activities. The findings indicate that digital banks provide significant benefits, including easier access to financial services, lower transaction costs, efficient budgeting features, and increased convenience in conducting cashless transactions. The novelty of this study lies in its specific focus on university students as a generation that is highly exposed to digital technology and increasingly dependent on digital financial services. Unlike previous studies that primarily examined digital banking from a general consumer perspective, this research highlights the relationship between digital banking adoption and students’ financial literacy, spending habits, and financial independence. The implications for education are substantial, as the findings emphasize the need to integrate digital financial literacy into higher education curricula to help students make informed financial decisions. Furthermore, this study can serve as a valuable reference for future research exploring digital financial innovation, student financial behavior, and technology-based financial education in diverse educational contexts.